A Syntactic Analysis of Constituent Structure in Sentences Written by EFL Students - Sari, Lilis Indah; Bochari, Siska; Usman, Sriati; Hastini, Hastini (Faculty of Humanities, Universitas Jenderal Soedirman, 2024)
This research aims to determine which student uses the most dominant conjunction, what students use the most difficult conjunction and why they have difficulty using correlative and coordinating conjunctions in their sentences. The population of this research was the 4th-semester students of the English education study program at Tadulako University. The sample was selected using a simple random sampling technique, and there were 151 4th-semester students. The researcher used a quantitative description. The data of this research used a test and questionnaire. The results of the data analysis show that (1) the most dominant conjunction used by the students was coordinating conjunction, especially conjunction “and” (2) the most difficult conjunction utilized by the students was correlative conjunction, namely conjunction “both…and”, the frequency of conjunction “both…and”, (3) there are two factors influencing the students in using coordinating and correlative conjunctions which are internal factor and external factor. The internal factors are: the students rarely improve their knowledge about conjunctions; The students are not interested in the material about conjunctions; The students do not understand the function of conjunctions; The students do not understand about lexical categories. The external factors are: There is no motivation from lecturers or teachers for students to learn the conjunctions; The lecturers or the teachers do not explain clearly the material of conjunctions.